Quantifying water relations and evapotranspiration in pomegranate (Punica granatum L. var. wonderful) in response to salt stress - Bhantana, Parashuram; Lazarovitch, Naftali (Nepal Agriculture Research Journal, 2025)
Water availability and salinity are major abiotic factors limiting plant growth and productivity worldwide. So, development of a tool that can estimate plant water demand is of prime importance. In the current study the effects of salt stress on water relations and plant stress were measured and different models were tested for evapotranspiration (ET) estimation. The measurements included (ET), leaf water potential (LWP), electrolytic leakage (ECL), stomatal conductance (gs) and stomatal density (StoD) in lysimeter grown young pomegranate trees (Punica granatum L.) under salt stress. Trees were subjected to different irrigation treatments with electrical conductivities (ECiw) of 0.8, 2.8, 5.0 and 8.5 dS m-1 for two years (2008-2009). Estimation of ET was made based on the measured value of ET, LWP, ECL, gs and StoD. A significant reduction of ET, LWP, and gs were recorded with increasing ECiw from 0.8 to 8.5 dS m-1. In contrary, a significant increment in ECL and StoD was observed at higher saline treatment. Among four parameters studied, StoD and ECL correlated best with ET (R2 = 0.79 and 0.75). When a set of three factors was generated, the ET equation (ET = 14.77 – 0.015×StoD – 0.97× ECL + 0.005 × gs) described about 93% (R2 = 0.93) of the ET values and the model was significant at (F (3, 16) = 72.66, p<0.00001). The set of 3 factor model was stronger than the one to one factor correlation study. Since the measurement of ECL is relatively simple, an ECL generated equation for ET estimation is recommended for a practitioner. Moreover, a multiple factor model remains as an important tool for an agro-ecosystem modeling and long term ecological planning.